2009
DOI: 10.1177/1753193408090129
|View full text |Cite
|
Sign up to set email alerts
|

Palmar Fixation of Dorsally Displaced Distal Radius Fractures Using Locking Plates with Smartlock Locking Screws

Abstract: We performed a prospective cohort study on a consecutive series of 35 unstable, dorsally displaced distal radius fractures, which were treated with palmar locking plates and SmartLock locking screws. There were 17 men and 18 women with a mean age of 44 years who were reviewed at a mean follow-up of 10 months. All the fractures healed at a mean time of 7 weeks. Radiographs did not show any change in alignment from the initial postoperative period until fracture union. The average Mayo wrist score was 90 after f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
15
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 17 publications
2
15
0
Order By: Relevance
“…9,10,11,12,13,14,15,17) Furthermore, in our study, there were no mechanical complications such as irritations of flexor tendons or the median nerve. Some studies have reported on mechanical irritations after volar plate fixation 18,19,20).…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…9,10,11,12,13,14,15,17) Furthermore, in our study, there were no mechanical complications such as irritations of flexor tendons or the median nerve. Some studies have reported on mechanical irritations after volar plate fixation 18,19,20).…”
Section: Discussionsupporting
confidence: 52%
“…They reported that 12 patients showed excellent results and 28 patients showed good results after a mean follow-up of 12 months, according to the Gartland and Werley scoring system. Wong et al11) reported the results from 35 patients with dorsally displaced distal radius fractures treated using the Stryker plating system with SmartLock locking screws after a mean follow-up of 10 months. The mean Mayo Clinic wrist score was 90 points and 20 patients achieved an excellent result.…”
Section: Discussionmentioning
confidence: 99%
“…16,19 Reports are accumulating in the literature on the clinical and radiological performance of various palmar locking plates with broadly distributed qualities and subtle differences in specific implant characteristics. [1][2][3][4]6,7,[9][10][11][12]16 The multiplicity of reports in the literature and new implant designs results in more options for choosing an appropriate treatment strategy and, therefore, hints at an increased autonomy and potential for creativity in individual surgeons. Personal prefer- ence and experience should influence these considerations.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have reported that palmar plate fixation is an effective option for most types of distal radius fractures. [1][2][3][4][5][6][7][8] Using an interlocking fixation system results in good patient satisfaction and wrist function and restoration of physiological radius length and axis function. [1][2][3][4][9][10][11][12] Several analyses could not reveal that locking compression plates providing angular stability are superior in terms of biomechanical performance when compared with conventional nonlocking fixation systems.…”
mentioning
confidence: 99%
“…Complications have been reported due to overpenetration of screws through the dorsal cortex, intraarticular penetration and radial artery injury. Variable angle locking screws may help in prevention of joint penetration and interference with other hardware [107]. Fracture settling due to inadequate support of the subchondral bone by the distal screws can also occur [91,[108][109][110][111][112].…”
Section: Distal Radiusmentioning
confidence: 99%